Impact of Self-Reported Family History on Some Metabolic Markers of Type 2 Diabetic Patients - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Family history of type 2 diabetes mellitus (T2DM), hypertension (HTN) and obesity, are known non-modifiable, independent and easily assessed risk factors for incident type 2 diabetes.Aims:This study was aimed at assessing the effect of self-reported family history on the levels of some metabolic markers (total homocysteine [tHcy], high sensitivity C-reactive protein [hs-CRP] and glycated haemoglobin [HbA1c]) among patients with type 2 diabetes.Settings and Design:Two hundred and forty participants subdivided into Group 1 (T2DM only), Group 2 (T2DM diagnosed with HTN) and Group 3 (controls) were enrolled in a cross-sectional pattern.Subjects and Methods:A structured questionnaire was used to obtain information on self-reported family history. Biochemical parameters were assayed using standard laboratory procedures.Statistical Analysis Used:SPSS version 20.0 was used for statistical analysis with significance atP≤ 0.05.Results:Group 1: Family history of type 2 diabetes (FHD) (HbA1c,P< 0.001, fasting plasma glucose [FPG],P= 0.005, triglycerides [TG],P= 0.049), family history of HTN (FHTN) (HbA1c,P< 0.001, FPGP= 0.005), family history of obesity (FHO) (HbA1c,P< 0.001, high-density lipoprotein cholesterol [HDL-C],P= 0.049). Group 2: FHD (tHcy,P= 0.021, HDL-C,P= 0.026), FHTN (tHcy,P= 0.035), FHO (HbA1c,P= 0.003, FPG,P= 0.001, TC,P< 0.001, TG,P= 0.019, LDL-C,P= 0.001). Group 3: FHD (tHcy,P= 0.004, HDL-C,P= 0.035), FHTN (FPG,P< 0.001, tHcyP= 0.010, TC,P= 0.037, TG,P= 0.003), FHO (hs-CRP,P< 0.001, HDL-C,P= 0.007, TGP= 0.001, LDL-CP= 0.019).Conclusions:Self-reported positive family history may provide insights into the biochemical and metabolic profile of patients with type 2 diabetes.